PROPAGANDA IKLAN LAYANAN MASYARAKAT (ILM) PADA MASA KEMERDEKAAN HINGGA MASA REFORMASI - Pujiyanto Pujiyanto (Gelar : Jurnal Seni Budaya, 2010)
Public service advertisement (ILM) is the one delivering information, persuasion or educating the public through advertising media in order to increase the people’s knowledge, attitude awareness and behavior change to the problem delivered, as well as to get the good image in the people mind. ILM occurs based on the state/people condition suffering from a social problem, so that the messages delivered is mostly social in nature. Viewed from Indonesian struggling history dialectics: 1) In Independence colonialism age with cooperative and revolutionary country because of ideology difference, ILM was the struggle political propaganda for uniting the nation and country. 2)In Old Order age with nationalism politics because of the confuse occurring among the rulers inclining to support the dominating; thus  ILM is nationalist political propaganda in nature function to eradicating the separatism movement. 3) In New Order age with paternalistic, that is, to look for people’s sympathizing to the governmental program, ILM is development political propaganda in nature functioning to support the successful governmental program. 4) In reformation age with pluralist liberalism, with nationality freedom, ILM is the critique for development functioning as the supervisor or monitor for the country’s condition. ILM always develops along with the development of people civilization, technology and problem occurring within the society. Key words : Independence age, Old Order, New Order, Reformation, Media, Public Service Advertisement, Propaganda.